Analisis Biaya dan Dampak Lingkungan dalam Proses Produksi Keramik: Studi Kasus UKM ABC - Inderawati, Maria Magdalena Wahyuni; Basudewa, Salomon Quarum; Magdalena, Riana; Sukwadi, Ronald (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
ABC Ceramic Factory conducted the process of producing ceramic floor tiles, distributing them to ceramic shops, and then selling them to consumers. Several processes or stages, from manufacturing to distribution, still leave abandoned waste. This research aims to determine what costs in making ceramics at the ABC Ceramic Factory can be reduced to save on company costs. The methods used are Green Quality Function Deployment and AHP Methods. Based on the data processing results, the ceramic manufacturing process is efficient, and the ceramic color is long-lasting because it has the expected satisfaction values of 0.661 and 0.538. Then, recycling waste is the highest technical response, with a value of 0.24. At the same time, the production process is the stage that produces the most waste, with a value of 0.29, and raw material costs are the costs that can be reduced the most, with the highest value of 4+2-. Therefore, the ABC Ceramic Factory must improve from the manufacturing process to the final product.